Pemerolehan Demensi Pengetahuan dalam Keterampilan Membaca Teks Bahasa Inggris Siswa Sekolah Menegah Atas - Muhammad Sulhan (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2019)
Anderson et al (2001) introduces the way to state educational objectives in the forms of a verb and a noun. The verb generally represents the intended cognitive process; that is, the kind of student’s behaviour to be developed, while the noun generally represents the kinds of knowledge to be expected and acquired by students; that is, the content in which this behaviour is to operate. This descriptive qualitative research aims to find out the kinds of knowledge acquired by students in the teaching of reading comprehension to SMA students. The data of the research is taken from the noun stated in the teachers’ questions and instructions which are then analyzed by using Anderson’s lists of knowledge dimension. The results show that acquired 46,15% of factual knowledge, 38,46% of conceptual knowledge, and 15.38%.of procedural knowledge. Keywords: educational objective, kinds of knowledge, reading comprehension skill